2017
DOI: 10.7717/peerj.3360
|View full text |Cite
|
Sign up to set email alerts
|

Storm effects on intertidal invertebrates: increased beta diversity of few individuals and species

Abstract: Climate change is predicted to lead to more extreme weather events, including changes to storm frequency, intensity and location. Yet the ecological responses to storms are incompletely understood for sandy shorelines, the globe’s longest land-ocean interface. Here we document how storms of different magnitude impacted the invertebrate assemblages on a tidal flat in Brazil. We specifically tested the relationships between wave energy and spatial heterogeneity, both for habitat properties (habitat heterogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…Amaral et al () investigated the intertidal macrofauna of both beaches and found that the number of species and abundance of individuals in Araçá Bay was more than double that observed at Barequeçaba. Similarly, Corte, Checon, et al (), Corte, Schlacher, et al () registered hundreds of macrofaunal species at Araçá, including higher numbers of polychaetes, molluscs, and crustaceans, whereas Nucci et al () registered only three species of Crustacea at Barequeçaba. The larger abundance of feeding items at Araçá, and more selective and constant feeding behavior by individuals of O. minuta at this site, may also explain the very high production and turnover (production/biomass) ratio observed by Petracco et al (), which is one of the highest found so far for sandy beach gastropods.…”
Section: Discussionmentioning
confidence: 93%
“…Amaral et al () investigated the intertidal macrofauna of both beaches and found that the number of species and abundance of individuals in Araçá Bay was more than double that observed at Barequeçaba. Similarly, Corte, Checon, et al (), Corte, Schlacher, et al () registered hundreds of macrofaunal species at Araçá, including higher numbers of polychaetes, molluscs, and crustaceans, whereas Nucci et al () registered only three species of Crustacea at Barequeçaba. The larger abundance of feeding items at Araçá, and more selective and constant feeding behavior by individuals of O. minuta at this site, may also explain the very high production and turnover (production/biomass) ratio observed by Petracco et al (), which is one of the highest found so far for sandy beach gastropods.…”
Section: Discussionmentioning
confidence: 93%
“…surveys between pre‐Isaac and the third day after it landed, between the third and 14th day after the hurricane, and so on). We used a Bray–Curtis distance measure to calculate a dissimilarity index for each site (Corte et al , Vokurkova et al ), and ternary plots to visualize the relative contribution of the three components of β diversity to overall differences between consecutive time periods. In the ternary plots, values of replacement, abundance difference, and similarity decide the position of each dot (representing the difference in community structure measured between consecutive time periods) in the plot.…”
Section: Methodsmentioning
confidence: 99%
“…Although storms are expected to enhance erosive processes and directly kill macroinvertebrates (Mclachlan et al 1996), studies have suggested that several macrofaunal species, mainly detritivorous ones, as the crustacean E. braziliensis, are resilient to moderate events on non-urbanized sandy beaches, regardless of morphodynamics (Alves and Pezzuto 2009, Harris et al 2011, Machado et al 2016. As suggested by other authors (Machado et al 2016, Corte et al 2017, storm wave events may enhance both redistribution of sediment fauna and productivity at sandy shores, reducing competition and increasing macrofauna richness, density and diversity. Moderate storms may increase short-term deposition of organic detritus (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…However, dissipative and undisturbed beach populations may also be controlled by ecological interactions (e.g., density-dependent mechanisms) (Defeo and Mclachlan 2005). Other environmental conditions are thought to be important drivers of the community structure of the macrofauna, including temperature (Taylor and Mclachlan 1980), food availability (Bergamino et al 2013), and natural disturbances such as storms (Harris et al 2011, Machado et al 2016, Corte et al 2017 and rainfall Defeo 1999, 2015).…”
Section: Introductionmentioning
confidence: 99%